Hydrodynamic measurements around moving bodies - Samson, M. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This applied session will proceed in the Pprime Institute of Poitiers. This Institute is a research unit whose topics are Physics and Mechanics of Materials, FluidThermal-Combustion, Mechanical Engineering and Complex Systems. These issues are addressed through experimentation, numerical simulation and theoretical modeling. Within this Institute are grouped two axes, RoBioSS and HydEE, which respectively investigate the biomechanics of sports and the hydrodynamics of flows. It is at the crossroads of these two teams that are located this applied session entitled "Hydrodynamic measurements around moving bodies". The objective of this session is to present kinematic and dynamic measuring tools to analyse the flow around a solid in motion, especially around the arms of swimmer, in front crawl.